The Relationship between Students’ Learning Motivation and Their Learning Achievement in Mathematics - Neman, Meily Ivane Esther; Surdado, Melsin (11th International Scholars Conference, 2017)
This quantitative research aims to measure the level of students’ learning motivation, their learning achievement in mathematics, and also to find out the relationship between the students’ learning motivation and their learning achievement in mathematics. In data analysis, the researcher employed the descriptive and correlation method. The instrument for data collection was a questionnaire that consisted of 36 questions and the respondent were 88 grade VIII students from a Junior High School in North Minahasa. The sampling technique used in this study was convenience sampling method. The results shows that the level of students’ learning motivation is high (Mean = 3.99), and the level of their learning achievement in Mathematics is good (Mean = 74.93). It is also found out that there is no significant relationship between the students’ learning motivation and their learning achievement in mathematics. Thus, it is recommended for the teacher and the students to maintain the way of learning and teaching in order to keep their learning achievement in Mathematics.